Heavy Water Models for Classical Molecular Dynamics: Effective Inclusion of Nuclear Quantum Effects - Chamorro, Victor Cruces; Tempra, Carmelo; Jungwirth, Pavel (The journal of physical chemistry. B, 2021)
Small differences in physical and chemical properties of H2O and D2O, such as melting and boiling points or pKa, can be traced back to a slightly stronger hydrogen bonding in heavy versus normal water. In particular, deuteration reduces zero-point vibrational energies as a demonstration of nuclear quantum effects. In principle, computationally demanding quantum molecular dynamics is required to model such effects. However, as already demonstrated by Feynmann and Hibbs, zero-point vibrations can be effectively accounted for by modifying the interaction potential within classical dynamics. In the spirit of the Feymann-Hibbs approach, we develop here two water models for classical molecular dynamics by fitting experimental differences between H2O and D2O. We show that a three-site SPCE-based model accurately reproduces differences between properties of the two water isotopes, with a four-site TIP4P-2005/based model in addition capturing also the absolute values of key properties of heavy water. The present models are computationally simple enough to allow for extensive simulations of biomolecules in heavy water relevant, for example, for experimental techniques such as NMR or neutron scattering.